Electricity losses in the distribution network in Brazil (Research, Society and Development, 2022)
The losses of electricity in an electricity distribution network, has received increasing attention from power concessionaires around the world. In Brazil, each year, regulatory measures are increasingly rigid, due to the tariff increase. This is due to the request for an energy demand, causing losses, in the transport of cargo that part of the energy that is lost in this path causing damage to the energy concessionaire and the consumer, has to bear the total costs requested, including energy losses, along this trajectory. Given this scenario, the energy concessionaires have been looking for ways to combat energy waste, installing new measurement technologies, to have greater control of electricity and by traveling the path from the hydroelectric plant to the substation to its final destination consumption. It suffers a significant loss of electrons, causing the final consumer to pay in his electricity bill for an improper request. Currently in Brazil, little is known about the losses of electricity and how they work. The energy concessionaires, not to pay a high amount, distribute this value to the consumer units. One way to combat and better the demand of energy, is by investing in highly qualified equipment, to control the demands of energy, thus it is possible to reduce the loss of electricity and improve the quality of life.